The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2011
DOI: 10.1002/pbc.22908
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and predictors of anthracycline cardiotoxicity in children treated for acute myeloid leukaemia: Retrospective cohort study in a single centre in the United Kingdom

Abstract: Background Anthracycline cardiomyopathy is of concern in children treated for acute myeloid leukaemia (AML), but there are few data on the incidence and natural history of cardiotoxicity after AML treatment in the United Kingdom, where regimens have included high anthracycline exposure. Procedure Prevalence and predictors of cardiotoxicity were retrospectively reviewed in 124 children treated on the MRC AML 10 and AML 12 trials in a single, large centre from November 1987 to September 2004. Subclinical cardiot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
40
3
2

Year Published

2011
2011
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(49 citation statements)
references
References 32 publications
2
40
3
2
Order By: Relevance
“…The same feature has already been published by Temming et al who reported a 12% prevalence of late cardiotoxicity after first-line treatment only versus 37% after first-line treatment plus salvage therapy for relapse. 12 The German group also underlined a high risk of late cardiotoxicity in patients who had been treated twice with anthracycline because of secondary AML, which is consistent with our results. 13 In transplanted children, when our study was restricted to patients who never experienced leukemia relapse, we did not detect any difference in late cardiotoxicity between those who received HSCT during their first CR and those treated with chemotherapy only.…”
supporting
confidence: 82%
See 1 more Smart Citation
“…The same feature has already been published by Temming et al who reported a 12% prevalence of late cardiotoxicity after first-line treatment only versus 37% after first-line treatment plus salvage therapy for relapse. 12 The German group also underlined a high risk of late cardiotoxicity in patients who had been treated twice with anthracycline because of secondary AML, which is consistent with our results. 13 In transplanted children, when our study was restricted to patients who never experienced leukemia relapse, we did not detect any difference in late cardiotoxicity between those who received HSCT during their first CR and those treated with chemotherapy only.…”
supporting
confidence: 82%
“…This feature of transient cardiomyopathy occurrence has already been reported in the German as well as in the UK experience of childhood AML survivors' late cardiotoxicity. 12,13 Although potentially reassuring, this concept of possible improvement must be interpreted with caution because long-term persistence of such an improvement cannot be predicted and will require longer follow up. In addition, we cannot exclude the possibility that some apparent improvements were, in fact, due to underestimation of cardiac function in a previous echocardiogram.…”
mentioning
confidence: 99%
“…More recent studies that included both the LV and RV reported functional deterioration also at RV [12,14]. It was recently reported that diastolic dysfunction can precede systolic dysfunction and the risk of diastolic dysfunction in RV is higher than that of LV [14,25]. In contrast, another recent study reported normal RV function and high LV MPI values in patients with early-stage anthracycline-induced cardiotoxicity [4].…”
Section: Discussionmentioning
confidence: 88%
“…Analysis from two pediatric AML studies (MRC AML10 and AML12) showed a prevalence of early and late cardiotoxicity of 14 and 17%, respectively, and there was a trend toward increased cardiotoxicity in patients who subsequently received salvage therapy [31]. In another pediatric analysis that included 1,207 AML patients <18 years of age treated in trials AML-BFM93/98, the cumulative incidence of cardiotoxicity at 11 years was 5% [32].…”
Section: Discussionmentioning
confidence: 99%